Peningkatan Pronunciation Melalui Artificial Intellegent Dalam Pembelajaran Bahasa Inggris Di Universitas Kadiri - Vitasmoro, Pamadya; Jatmiko, Jatmiko; Rahardini, Nimas Ayu (Sentra Cendekia, 2025)
Pronunciation is a critical component of spoken English proficiency, The advent of Artificial Intelligence (AI) technologies has introduced new possibilities for supporting pronunciation improvement in language learning. The objective of this research is to find out the improvement of students’ pronunciation ability through of AI-based applications. A quantitative experimental design was used, involving 30 students divided into an experimental group, which used an AI-based pronunciation , and a control group, which followed traditional pronunciation . The data were analyzed by using paired sample t-test then the effect size and improvement were calculted. The result of the study showed that experimental class had improvement of their Pronunciation ability. The experimental pre-test mean score was 45, while the control class' pre-test mean score was 30,7 based on statistical analysis. The Artificial Intelligence (AI) technologies was implemented in the experimental class, and the average score increased to 70.7 whereas the control class was 30. Based on the data the experimental class had a higher mean score in the post-test while the control class got the lower mean score, in conclusion using Artificial Intelligence (AI) technologies can improve student’s pronunciation ability.